The Francis Daniel Pastorius reader : writings by an early American polymath - Pastorius, Francis Daniel, 1651-1719 (Max Kade German-American Research Institute series., 2019)
"A comprehensive overview of the writings of Francis Daniel Pastorius, founder of Germantown, lawyer, educator, and early modern polymath. Includes many of Pastorius's unpublished manuscripts as well as new translations of German-language tracts printed in his lifetime"--Provided by publisher